Peabody Museum : imagining the future of the Yale Peabody Museum of Natural History - Helfand, Jessica, (SAGE Knowledge. Cases., 2018)
In 2018, the Yale Peabody Museum of Natural History was about to go through a massive renovation. The physical makeover would add exhibition, classroom, and storage space, as well as updating the museum's infrastructure. Unfortunately, the museum would have to close to the public during for the two years of construction. But when it emerged, what would the museum be? What is the role for a university natural history museum in the 21st century?